7 - Whither ‘Sub-Saharan Africa’ Can We Use the Compass Instead? - Kajula, Lusajo; Chachage, Chambi (CODESRIA Bulletin, 2023)
Currently, there are few conversations about the term ‘Sub-Saharan Africa (SSA)’ (L.T. 2019) and its continued use (Zeleza 2022; Daley and Murrey, 2022). An end to the use of this problematic term is long overdue, and African voices on this matter should be amplified. This contribution to the literature aims to offer a solid reference point to support discussions about the discontinued use of this virulent term due to its racialist origins and racist undertones (Adébísí 2016; Chachage 2020; Ekwe-Ekwe 2012; Zeleza 2010). Through the voices of several prominent Africans, we explore the term’s invention, its scholarly (dis)advantages, and potential harm in its continued usage.